A high temperature resistant antistatic agent and its application in film antistatic
By combining components such as PEDOT:PSS, conductive nanoparticles and aminated polysiloxane, the problem of failure of existing antistatic agents at high temperatures is solved, and the effect of maintaining excellent antistatic characteristics in the range of 20~250°C is achieved.
Patent Information
- Application Number
- CN202411490286.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-10-24
AI Technical Summary
Existing antistatic agents are prone to failure in high temperature environments and it is difficult to maintain stable antistatic properties at high temperatures.
The combination of poly3,4-ethylene dioxythiophene-polystyrene sulfonate (PEDOT:PSS), conductive nanoparticles, aminated polysiloxane, silicone surfactant and water is used to achieve stable dispersion of conductive nanoparticles in PEDOT:PSS aqueous solution by bridging the aminated polysiloxane.
The antistatic agent maintains excellent antistatic characteristics within the range of 20~250℃, meeting the application needs of high-temperature antistatic.
Smart Images

Figure CN118995045B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of functional materials, and particularly relates to a high temperature resistant antistatic agent and its application in film antistatic. Background Art
[0002] Antistatic agents are a type of additives that are added to plastic products or applied to the surface of films to reduce the accumulation of static electricity. Depending on the method of use, antistatic agents can generally be divided into two categories: additive type and external coating type. Among them, external coating antistatic agents have the advantages of simple operation and obvious antistatic effect. When this type of antistatic agent is applied to the surface of a polymer material, the lipophilic groups in the antistatic agent molecules will be adsorbed on the surface of the material. After drying, on the surface of the polymer material after the water is removed, the hydrophilic groups in the antistatic agent molecules are arranged toward the air side, which is easy to absorb environmental moisture, or combine with moisture in the air through hydrogen bonds to form a monomolecular conductive layer, so that the generated static charge leaks quickly to achieve the antistatic purpose.
[0003] However, most antistatic agents can only meet the application in normal temperature environment and are prone to failure in high temperature environment. For example, the Chinese patent with application number CN 201810451969.9 discloses a composite high-efficiency antistatic agent for plastics, whose main components are anion-modified polyaniline, cationic polymer antistatic agent and black phosphorene. When the temperature exceeds 100°C, anion-modified polyaniline is prone to cross-linking reaction and the conductive performance decreases. Chinese patent document CN202011393141.6 discloses "a method for preparing an environmentally friendly and durable antistatic agent for fabrics". This method is to introduce highly hygroscopic imidazole at the end of acrylic polyoxyethylene ether molecule and then graft it on hydrogen-containing siloxane. The antistatic agent is applied to the treatment of environmentally friendly and durable antistatic agents for fabrics, but because this type of antistatic agent contains polyoxyethylene ether, it degrades at 200°C, so it is difficult to maintain stable antistatic performance at high temperature. Therefore, how to prepare an antistatic agent with good stability and high temperature resistance through the formulation design of antistatic agents is of great value for the production of special antistatic materials in high temperature environments. Summary of the invention
[0004] In view of the defects of the prior art, the technical problem to be solved by the present invention is to provide a method for preparing an antistatic agent with excellent stability and high temperature resistance and its application in the antistatic treatment of polyimide films.
[0005] The present invention proposes a high temperature resistant antistatic agent and its application in film antistatic. First, an antistatic agent is provided. The composition of the antistatic agent includes: poly (3,4-ethylenedioxythiophene-polystyrene sulfonate) (PEDOT:PSS for short), conductive nanoparticles, amino polysiloxane, silicone surfactant and water. The conductive nanoparticles are stably dispersed in the PEDOT:PSS aqueous solution through the bridging effect of the amino polysiloxane on the PEDOT:PSS.
[0006] At the same time, PEDOT:PSS and conductive nanoparticles in this antistatic agent have good high-temperature stability, so they can meet the application of high-temperature antistatic and other fields. The antistatic agent can be applied to the surface of common polymer substrates by spraying, roller coating, etc. to improve its antistatic ability, especially in the range of 20~250℃, it can maintain excellent antistatic properties.
[0007] The antistatic agent comprises, by weight, 3 to 5 parts of PEDOT:PSS; 7 to 10 parts of conductive nanoparticles; 10 to 30 parts of amino polysiloxane; 2 to 5 parts of silicone surfactant; and 50 to 78 parts of water.
[0008] The conductive nanoparticles are any one of pretreated multi-walled or single-walled carbon nanotubes, graphene, and carbon black. The pretreatment process includes: placing the conductive nanoparticles in a NaNO3 and concentrated sulfuric acid solution with a mass ratio of 1:50, reacting at below 0°C for 2 hours, then adding potassium permanganate and reacting at 5~15°C for 0.5~1 hour, and finally pouring the above solution into deionized water for precipitation, and washing with deionized water to neutrality.
[0009] Preferably, the size of the pretreated conductive nanoparticles is 5-20 nm.
[0010] Wherein, the amino polysiloxane further comprises phenyl groups and silanol groups.
[0011] Preferably, the raw materials for preparing the amino polysiloxane include: amino-containing siloxane monomers, phenyl-containing siloxane monomers, and tetraethyl orthosilicate.
[0012] Wherein, the organic silicon surfactant is aminoethylaminopropyl polydimethoxysilane.
[0013] The amino polysiloxane acts as a bridge, and the PEDOT:PSS and the conductive nanoparticles in the antistatic agent are connected through the amino polysiloxane, thereby forming a uniform and stable dispersion state in the emulsion. Among them, the PEDOT:PSS and the amino hyperbranched siloxane are hydrogen bonds, while the conductive nanoparticles and the amino hyperbranched siloxane are chemical bonds.
[0014] In a second aspect, the preparation method of the above antistatic agent comprises:
[0015] S1. Disperse the formulated amount of PEDOT:PSS, conductive nanoparticles, and amino polysiloxane in water, and control the reaction temperature to 30-50°C under nitrogen protection. o C, and stir the reaction thoroughly for 0.5~1 h.
[0016] S2. Add the formulated amount of organosilicon surfactant to the aqueous solution of step S1, and react at 30-50° C. for 0.5-1 h to obtain a preliminary emulsion.
[0017] S3. Filter the preliminary emulsion in step S2 through a 1 μm or 5 μm filter to remove large particles of impurities.
[0018] In a third aspect, the use of the antistatic agent described above in antistatic modification of polymers.
[0019] In a fourth aspect, a modified polymer film comprises: a polymer film and the antistatic agent described above. Preferably, the polymer film is a polyimide film.
[0020] In a fifth aspect, the method for preparing the modified polymer film described above comprises: coating the antistatic agent described above on the surface of the polymer film.
[0021] Wherein, the above-mentioned coating method includes spray coating or roller coating.
[0022] Furthermore, the specific steps of spraying the above-mentioned antistatic agent on the surface of the polymer film include:
[0023] S1. The antistatic agent is evenly sprayed on the surface of the polymer film through a nozzle on the coating machine;
[0024] S2. The polymer film is continuously passed through an oven to quickly remove moisture so that the antistatic agent adheres to the surface of the film.
[0025] Preferably, in step 1, the spraying speed is adjusted to control the thickness of the sprayed antistatic agent to be 100-300 nm;
[0026] Preferably, the baking temperature in step 2 is 80-90°C.
[0027] The beneficial effects of the present invention are:
[0028] (1) Through structural design, PDOT:PSS and graphene are used as conductive components, and amino polysiloxane is designed and synthesized as a bridge to effectively compound PEDOT:PSS and graphene, thereby achieving long-term and stable dispersion of graphene in PEDOT:PSS aqueous solution.
[0029] (2) Through material screening and formula optimization, the developed antistatic agent can still maintain excellent antistatic properties in the high temperature range of 20~250℃, meeting the application requirements of high temperature antistatic.
[0030] (3) The conductive PEDOT:PSS component is compounded on the surface of a polymer film such as polyimide through amino polysiloxane. Through multiple interactions such as hydrogen bonds or chemical bonds between amino polysiloxane and polyimide chain segments, the long-lasting antistatic effect of this type of antistatic agent is achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of amino-polysiloxane-bridged PEDOT:PSS and conductive nanoparticles. DETAILED DESCRIPTION
[0032] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0033] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0034] If the specific experimental conditions are not specified in the examples, they are usually based on the conventional conditions in the field or the conditions recommended by the reagent company; the materials, reagents, etc. used in the examples can be purchased through commercial channels unless otherwise specified.
[0035] The above-mentioned PEDOT:PSS was provided by Merck Chemicals, graphene and carbon nanotubes were provided by Chengdu Organic Chemistry Co., Ltd., Chinese Academy of Sciences, and carbon black was provided by Cabot.
[0036] The surface resistance of the antistatic agent coated on the polyimide film was tested by a Filmetrics R50-EC sheet resistance tester produced by KLA.
[0037] Preparation of amino polysiloxane: Three raw materials, γ-aminopropylmethyldimethoxysilane, phenyltrimethoxysilane and tetraethyl orthosilicate, are mixed evenly in a molar ratio of 1:1:1, and a water / ethanol mixed solvent (mass ratio of 1:1) with the same weight as the total weight of the three raw materials is added as a solvent for dissolution, and then 0.5wt% of the total weight of the three raw materials as a catalyst dibutyltin dilaurate is added, and the temperature is raised to 80°C and reacted for 3h to obtain amino polysiloxane.
[0038] Embodiment 1:
[0039] Under nitrogen protection, 5 parts of PEDOT:PSS, 7 parts of graphene, and 10 parts of amino polysiloxane were dispersed in 75 parts of water by mass, the reaction temperature was controlled at 30°C, and the reaction was stirred for 0.5 h; then 3 parts of organosilicon surfactant aminoethylaminopropyl polydimethoxysilane were added to the above reaction aqueous solution, and the reaction was continued at 30°C for 1 h; the above synthesized preliminary emulsion was filtered through a 1 μm filter to remove large particles of impurities in the emulsion, and an antistatic agent was synthesized. The above antistatic agent was continuously and evenly sprayed on the surface of the polyimide film through a spraying device, and baked at 80°C for 10 min, and the thickness of the antistatic agent was controlled to be 150 nm.
[0040] Embodiment 2:
[0041] Under nitrogen protection, 5 parts of PEDOT:PSS, 10 parts of carbon nanotubes, and 10 parts of amino polysiloxane were dispersed in 72 parts of water by mass, the reaction temperature was controlled at 30°C, and the reaction was stirred for 0.5 h; then 3 parts of organosilicon surfactant aminoethylaminopropyl polydimethoxysilane were added to the above reaction aqueous solution, and the reaction was continued at 30°C for 1 h; the above synthesized preliminary emulsion was filtered through a 1-micron filter to remove large particles of impurities in the emulsion, and an antistatic agent was synthesized. The above antistatic agent was continuously and evenly sprayed on the surface of the polyimide film through a spraying device, and baked at 80°C for 10 minutes, and the thickness of the antistatic agent was controlled to be 200 nm.
[0042] Embodiment 3:
[0043] Under nitrogen protection, 3 parts of PEDOT:PSS, 7 parts of graphene, and 20 parts of amino polysiloxane were dispersed in 67 parts of water by mass, and the reaction temperature was controlled at 50 o C, fully stirred and reacted for 0.5 h; then 3 parts of organosilicon surfactant aminoethylaminopropyl polydimethoxysilane were added to the above reaction aqueous solution, and the reaction was continued at 30°C for 1 h; the above synthesized preliminary emulsion was filtered through a 1 micron filter to remove large particles of impurities in the emulsion, and an antistatic agent was synthesized. The above antistatic agent was continuously and evenly sprayed on the surface of the polyimide film through a spraying device, and then heated at 80 oC for 10 min and control the thickness of the antistatic agent to be 150 nm.
[0044] Embodiment 4:
[0045] Under nitrogen protection, 5 parts of PEDOT:PSS, 10 parts of carbon black, and 10 parts of amino polysiloxane were dispersed in 72 parts of water, and the reaction temperature was controlled at 50 o C, fully stirred and reacted for 0.5 h; then 5 parts of organosilicon surfactant aminoethylaminopropyl polydimethoxysilane were added to the above reaction aqueous solution, and the reaction was continued at 30°C for 1 h; the above synthesized preliminary emulsion was filtered through a 1 micron filter to remove large particles of impurities in the emulsion, and an antistatic agent was synthesized. The above antistatic agent was continuously and evenly sprayed on the surface of the polyimide film through a spraying device, and then heated at 80 o C for 10 min and control the thickness of the antistatic agent to be 200 nm.
[0046] Comparative Example 1:
[0047] Under nitrogen protection, 5 parts of PEDOT:PSS and 10 parts of amino polysiloxane were dispersed in 82 parts of water, and the reaction temperature was controlled at 30 o C, fully stirred and reacted for 0.5 h; then 3 parts of organosilicon surfactant aminoethylaminopropyl polydimethoxysilane were added to the above reaction aqueous solution, and the reaction was continued at 30°C for 1 h; the above synthesized preliminary emulsion was filtered through a 1 micron filter to remove large particles of impurities in the emulsion, and an antistatic agent was synthesized. The above antistatic agent was continuously and evenly sprayed on the surface of the polyimide film through a spraying device, and then heated at 80 o C baking for 10 min, controlling the thickness of the antistatic agent to be 150nm.
[0048] Comparative Example 2:
[0049] Disperse 7 parts of graphene and 10 parts of amino polysiloxane in 80 parts of water, control the reaction temperature to 30°C, and stir the reaction for 0.5 h; then add 3 parts of organosilicon surfactant aminoethylaminopropyl polydimethoxysilane to the above reaction aqueous solution, and continue the reaction at 30°C for 1 h; filter the above synthesized preliminary emulsion through a 1 micron filter to remove large particles of impurities in the emulsion, and synthesize an antistatic agent. The above antistatic agent is continuously and evenly sprayed on the surface of the polyimide film through a spraying device, and at 80 o C for 10 min and control the thickness of the antistatic agent to be 150 nm.
[0050] Comparative Example 3:
[0051] Under nitrogen protection, 5 parts of PEDOT:PSS and 7 parts of graphene were dispersed in 85 parts of water by mass, the reaction temperature was controlled at 30°C, and the reaction was stirred for 0.5 h; then 3 parts of aminoethylaminopropyl polydimethoxysilane, an organic silicone surfactant, was added to the above reaction aqueous solution, and the reaction was continued at 30°C for 1 h; the above synthesized preliminary emulsion was filtered through a 1-micron filter to remove large particles of impurities in the emulsion, and an antistatic agent was synthesized. The above antistatic agent was continuously and evenly sprayed on the surface of the polyimide film through a spraying device, and baked at 80°C for 10 min, and the thickness of the antistatic agent was controlled to be 150nm.
[0052] The performance comparison results of the antistatic agents prepared in Examples 1-4 and Comparative Examples 1-3 are shown in Table 1:
[0053] Table 1
[0054]
[0055] Through the analysis of the experimental data in Table 1, it can be seen that Examples 1-4 prepared high temperature resistant antistatic agents containing PEDOT:PSS, amino polysiloxane, conductive nanoparticles and silicone surfactants. Compared with Example 1, no conductive nanoparticles were added in Comparative Example 1, so its antistatic ability was weaker than that of Example 1, especially in a high temperature environment, the surface resistance increased sharply; in Comparative Example 2, no PEDOT:PSS was added, and the conductive nanoparticles were difficult to disperse stably in the emulsion, and precipitation occurred. There was no conductive component of PEDOT:PSS, so the antistatic ability was lower than that of Example 1; and in Comparative Example 3, no amino polysiloxane as a stabilizer was added, which also led to unstable dispersion of conductive nanoparticles and rapid attenuation of antistatic ability at high temperatures.
[0056] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments, or to perform equivalent replacements on parts thereof. Any modifications, equivalent replacements, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention. Although the above describes the specific implementation methods of the present invention, it is not intended to limit the protection scope of the present invention. Those skilled in the art should understand that, based on the technical solution of the present invention, various modifications or deformations that can be made by those skilled in the art without creative labor are still within the protection scope of the present invention.
Claims
1. An antistatic agent, characterized in that The antistatic agent comprises: poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, conductive nanoparticles, amino polysiloxane, organic silicon surfactant and water; The antistatic agent comprises, by weight, 3 to 5 parts of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate; 7 to 10 parts of conductive nanoparticles; 10 to 30 parts of amino polysiloxane; 2 to 5 parts of organosilicon surfactant; and 50 to 78 parts of water. The amino polysiloxane contains phenyl and silanol groups; the raw materials for preparing the amino polysiloxane include: amino-containing siloxane monomers, phenyl-containing siloxane monomers, and tetraethyl orthosilicate; The conductive nanoparticles are carbon nanotubes, graphene or carbon black; The organosilicon surfactant is aminoethylaminopropyl polydimethoxysilane; The preparation method of the antistatic agent comprises: S1, dispersing the formulated amount of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonate, conductive nanoparticles, and amino polysiloxane in water, and controlling the reaction temperature to 30-50° C. under nitrogen protection, and fully stirring the reaction for 0.5-1 h; S2, adding a formulated amount of an organosilicon surfactant to the aqueous solution obtained in step S1, and reacting at 30-50° C. for 0.5-1 h to obtain a preliminary emulsion; S3. Filter the preliminary emulsion in step S2 through a 1 μm or 5 μm filter to remove large particles of impurities.
2. Use of the antistatic agent according to claim 1 in antistatic modification of polymers.
3. A modified polymer film comprising: A polymer film and the antistatic agent according to claim 1.
4. The modified polymer film according to claim 3, characterized in that The polymer film is a polyimide film.
5. The method for preparing the modified polymer film according to any one of claims 3 to 4, comprising: Coating the antistatic agent according to claim 1 on the surface of the polymer film; Wherein, the coating method includes spraying or roller coating.
6. The preparation method according to claim 5, characterized in that: The specific steps of the spraying include: S1, the coating machine sprays the antistatic agent evenly on the surface of the polymer film through a nozzle; S2. The polymer film is continuously passed through an oven to quickly remove moisture so that the antistatic agent adheres to the surface of the film.
Citation Information
Patent Citations
A composite high-efficiency antistatic agent for plastics
CN108587111B
A method for preparing an environmentally friendly and durable antistatic agent for fabrics.
CN112522955B
Aqueous graphene electric-conduction coating material and applications thereof
CN109929371A